Defining the scope of extended NIPS in Western China: evidence from a large cohort of fetuses with normal ultrasound scans - Lin Chen; Li Wang; Yang Zeng; Daishu Yin; Feng Tang; Dan Xie; Hongmei Zhu; Hongqian Liu; Jing Wang (BMC, 2023)
Abstract Background Standard noninvasive prenatal screening(NIPS) is an accurate and reliable method to screen for common chromosome aneuploidies, such as trisomy 21, 18 and 13. Extended NIPS has been used in clinic for not only aneuploidies but also copy number variants(CNVs). Here we aim to define the range of chromosomal abnormalities that should be able to identify by NIPS in order to be an efficient extended screening test for chromosomal abnormalities. Methods A prospective study was conducted, involving pregnant women without fetal sonographic structural abnormalities who underwent amniocentesis. Prenatal samples were analyzed using copy number variation sequencing(CNV-seq) to identify fetal chromosomal abnormalities. Results Of 28,469 pregnancies included 1,022 (3.59%) were identified with clinically significant fetal chromosome abnormalities, including 587 aneuploidies (2.06%) and 435 (1.53%) pathogenic (P) / likely pathogenic (LP) CNVs. P/LP CNVs were found in all chromosomes, but the distribution was not uniform. Among them, P/LP CNVs in chromosomes 16, 22, and X exhibited the highest frequencies. In addition, P/LP CNVs were most common on distal ends of the chromosomes and in low copy repeat regions. Recurrent microdeletion/microduplication syndromes (MMS) accounted for 40.69% of total P/LP CNVs. The size of most P/LP CNVs (77.47%) was < 3 Mb. Conclusions In addition to aneuploidies, the scope of extended NIPS should include the currently known P/LP CNVs, especially the regions with recurrent MMS loci, distal ends of the chromosomes, and low copy repeat regions. To be effective detection should include CNVs of < 3 Mb. Meanwhile, sufficient preclinical validation is still needed to ensure the clinical effect of extended NIPS.